SERAMBI MADINAH YANG BERKARAKTER: PERAN BOLA BASKET DALAM MEMBENTUK GENERASI MUDA GORONTALO - I Kadek Suardika; Hartono Hadjarati; Rifky Mile; Agung Prasetyo; Safri Irawan; Zenab Nihe (STKIP Melawi, 2026)
Abstract: This study aims to analyze the role of basketball in character building for the youth generation in Gorontalo Province, known as the